The Role of Digital Media and Inquiry-Based Models in Chemistry Education: A Systematic Literature Review - Elisabeth Pistio Indah Saraswati; Muntholib; Nazriati (Universitas Syiah Kuala, 2026)
Chemistry education in the digital age requires innovations that can improve conceptual understanding, higher-order thinking skills (HOTS), and student engagement in the learning process. This study aims to conduct a systematic literature review to synthesize empirical findings related to the use of digital media, inquiry-based learning, and the integration of both in chemistry education. The study was conducted in accordance with PRISMA guidelines by selecting articles published between 2021 and 2025 from the scopus, ERIC, and google scholar databases. A total of 34 articles met the inclusion criteria and were analyzed using descriptive thematic analysis techniques. The results showed three patterns of integration: sequential, embedded, and enhanced integration. Digital media served as visualization tools, experiential learning, and pedagogical enhancement, while inquiry had three main roles: model-based inquiry, context-driven inquiry, and practice-focused inquiry. The integration of the two had a positive impact on cognitive outcomes, HOTS, and affective outcomes. The limitations of this study include the publication range of 2021–2025, the use of three databases, and descriptive analysis without quantitative meta-analysis. Overall, the integration of digital media and inquiry approaches has great potential in realizing meaningful and relevant chemistry learning in line with the demands of the 21st century, with effectiveness depending on the suitability of technology, pedagogical strategies, and learning objectives